HLA-based time management and synchronization framework for lean manufacturing tools evaluation. (April 2023) - Possik, Jalal; Zacharewicz, Gregory; Zouggar, Anne; Vallespir, Bruno
Discrete event simulation (DES) is a method for digitally replicating the behavior and performance of real-world processes, systems, and facilities. DES is widely applied in manufacturing, logistics, healthcare, and military domains. In some cases, DES method is insufficient. On one hand, the simulation must be disassembled into subsystems and then distributed on a multiprocessing environment to enhance the simulation performance. On the other hand, to expand current functionality and prevent future application development, a set of interacting simulations is required. In this project, the IEEE high-level architecture (HLA) standard mechanisms are adopted to solve the interoperability problems between heterogeneous components. Time synchronization between federates is essential to have all DESs running in parallel. In this paper, we present a distributed simulation framework designed to assist decision-makers in making the best decisions and prioritizing the adoption of Lean tools and techniques.